Essentials of ecology - Townsend, Colin R. (Blackwell Science, 2000)
Presents a balanced overview of ecology, with examples drawn from terrestrial and aquatic environments and a variety of organism types. Outlines the major tenets of ecology in a concise and simplified manner for the introductory level student. Softcover. DLC: Ecology.